PELAKSANAAN EKSEKUSI OBJEK JAMINAN FIDUSIA BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 DI PT PEGADAIAN KANTOR WILAYAH II KOTA PEKANBARU - Rachmat, Devie; Pratiwi, Ade; Suhendro, Suhendro (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In line with the government's program to encourage lending to small businesses and the weak economic class which is the largest part of the Indonesian people. So it is expected that with credit based on fiduciary system can help both credit recipients and creditors. One of the parameters of a good material debt guarantee is when the right of guarantee can be executed quickly with a simple, efficient process and contains legal certainty. The specific target of this study is to explain the problem solving about the implementation of Fiduciary Guarantee Object Execution Based on the Decision of the Constitutional Court No. 18/PUU-XVII/2019 at PT Pegadaian KantorWilayah II Pekanbaru City.